Analysis of structural stability and optoelectronic properties of new direct band gap halide double perovskites Cs2XRhCl6 : X=Na, K — a first principle study. (1st November 2022) - Dar, Suhail A.; Want, Basharat
Abstract: A precise and systematic analysis of C s 2 X R h C l 6 : X = N a, K was performed to investigate structural stability, optical and electrical properties using Density Function Theory simulations. Generalized Gradient Approximation(GGA) approximations were used to optimize the lattice constants. The stability of these double perovskites was governed by structural optimization, tolerance factor, and mechanical stability parameters which confirm their cubic structure stability in FM 3 ̄ M symmetry. The lattice stability reported through this investigation were in good agreement with previously synthesized, and analyzed double perovskites, like C s 2 A g B i X 6 (X = Cl, Br). Mechanical stability was obtained from elastic constants and the results of Pugh's (B/G) and Poisson's ( σ ) ratio gives the brittle nature of these Double Perovskites. The positive phonon dispersion considerably support the thermodynamic stability of C s 2 N a R h C l 6, however C s 2 K R h C l 6 is shown as thermodynamically unstable, although the elastic moduli values suggesting that both the systems under examination is mechanically stable. The measured electronic bandstructure indicates a direct bandgap along with semiconducting nature, for both GGA and modified Becke Jonhson's approximations. The electronic transition from the top of valence band [ C l ( 3 p ) + R h ( 4 d ) ] to the bottom of conduction band [ C l ( 3 p ) + R h ( 4 d ) ] is fundamentally direct at the X-point of the first Brillouin zone, as suggested by the band structure and density of states. The Calculated value of bandgap using mBJ potential is 1.79 eV for C s 2 N a R h C l 6 and 1.83 eV for C s 2 K R h C l 6 . Important optical parameters, like dielectric constant, absorption coefficient, energy loss function, reflectivity, and optical conductivity have been computed and discussed in detail. Visible and UV frequency absorption by these materials indicates potential applications in the optoelectronics industry. We were able to show that C s 2 N a R h C l 6 is plausible candidate material for photoelectric applications due to its significant refractive index and strong absorption coefficient in the range of 2.0-5.0 eV. For potential optoelectronic applications, the theoretical results may help in developing these lead-free Double Perovskites. Highlights: The DFT studies confirm the structural stability of double perovskites(DPs) Cs2XRhCl6 : X = Na, K. The thermodynamic stability of the materials under study is ensured by the negative value of enthalpy of formation. The semiconducting direct band gap is shown from both GGA and mBJ calculations by the DPs. The mechanical parameters shows brittle nature to these DPs. The debye temperature calculated from mechanical parameters are 254K and 225K for corresponding Na- and K-based DPs. The studied optical properties confirms that these DPs may be used in the both visible as well as UV region of spectrum. So, these may have broader applications in optoelectronic industry. The findings may be beneficial for experimentalists to prepare these type of DPs in laboratories for commercial uses.